Do enhanced sexual health services meet the needs of men who have sex with men?. (March 2013) - Dabrera, G; Johnson, S A; Bailey, A C; Cassell, J A
Enhanced Sexual Health Services (ESHS) have the potential to widen access to sexual health services for populations in England. This study aimed to identify what provision was commissioned in ESHS for men who have sex with men (MSM). We undertook a web-based survey of Primary Care Trust (PCT) commissioners in the southeast of England, exploring what sexual health services were commissioned for MSM and comparing them with published standards. Fourteen of 17 PCTs (82%) responded. All PCTs identified at least one genitourinary (GU) medicine clinic and 13 identified at least one ESHS commissioned for their population. However no single ESHS provided the full range of essential services for MSM. Testing for Chlamydia (84.6% PCTs) and for HIV (69.2% PCTs) were most commonly provided in ESHS, while only 46% and 62% of PCTs had an ESHS commissioned to provide gonorrhoea testing and hepatitis B/syphilis serology testing respectively. Under two-thirds reported training of staff in the sexual health needs of MSM. ESHS are not commissioned to provide the full range of essential sexual health services for MSM. This needs to be addressed by improving staff training in these services and strengthening care pathways between ESHS and GU medicine clinics.